2008
DOI: 10.1364/oe.16.006233
|View full text |Cite
|
Sign up to set email alerts
|

Non-collinear high harmonic generation: a promising outcoupling method for cavity-assisted XUV generation

Abstract: We present first experimental results of our investigation of non-collinear high harmonic generation (NCHHG) with a chirped pulse amplification system. Collimated high harmonic radiation of higher than 9th order is observed along the bisector of two fundamental beams crossing in a xenon gas target. The obtained results show that cavity-assisted non-collinear high harmonic generation is a promising candidate for efficient generation and outcoupling of extreme ultraviolet (XUV) radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…An important recent application is in extreme ultraviolet frequency comb metrology where a noncollinear control pulse switches high-harmonic radiation from a buildup cavity [23].…”
mentioning
confidence: 99%
“…An important recent application is in extreme ultraviolet frequency comb metrology where a noncollinear control pulse switches high-harmonic radiation from a buildup cavity [23].…”
mentioning
confidence: 99%
“…The technique allows generating high harmonics in a direction which is non-collinear with the driving beam [189]. In this case, two circulating DF pulses inside the cavity overlap temporally and spatially in a gas jet.…”
Section: Non-collinear Hhgmentioning
confidence: 99%
“…The process of non-collinear HHG is poorly investigated and may result in conversion efficiencies much lower than those of a standard HHG with a single fundamental beam. Moreover, the output coupling efficiency of this method is limited by the cavity design [189]. Implementation of this method presents a major challenge.…”
Section: Non-collinear Hhgmentioning
confidence: 99%
“…Moreover, the emitted harmonics can be spatially separated from the fundamental driving laser beams [34][35][36], allowing samples to be placed close to the generation region, where the harmonic fluence is high, without being damaged by the driving laser. Previous investigations of noncollinear HHG have also probed the nonlinear optics of the HHG process [37] and shown that this is a promising geometry for cavity-assisted HHG [38][39][40]. Other work has used the noncollinear geometry to produce spectrally narrow EUV light [41] and applied a noncollinear probe beam to spatially and temporally characterize attosecond pulses [42].…”
Section: Introductionmentioning
confidence: 99%